Understory Vegetation in Oil Palm Plantations Promotes Leopard Cat Activity, but Does Not Affect Rats or Rat Damage - Hood, Amelia S. C.; Aryawan, A. Agung K.; Advento, Andreas D.; Purnomo, Dedi; Wahyuningsih, Resti; Luke, Sarah H.; Ps, Sudharto; Snaddon, Jake L.; Foster, William A.; Caliman, Jean-Pierre; Turner, Edgar C.; Naim, Mohammad (Frontiers in Forests and Global Change, 2019)
The expansion of oil palm (Elaeis guineensis) plantations is a primary cause of land-use change and biodiversity loss in Southeast Asia. This has led to an increasing demand for the development of more sustainable agricultural management practices in plantations, such as Integrated Pest Management. Although populations of carnivorous mammals show declines when forest is converted to oil palm, some species, such as Leopard Cats (Prionailurus bengalensis) have been found to persist. They are often encouraged by plantation managers for their conservation value, and as agents of pest control to manage rat populations. Despite this, little is known about whether they reduce pest rat numbers, or whether plantation management affects how they use the oil palm habitat. This study was based at the Biodiversity and Ecosystem Function in Tropical Agriculture (BEFTA) Programme in mature oil palm plantations in Riau, Sumatra, where there are three management strategies altering understory vegetation structure. We quantified Leopard Cat activity, invasive rat abundance and rat damage using camera traps, live traps, and visual estimates respectively. We collected data over a four-year period, before and after the management strategies were applied. We recorded three species of wild mammals (Leopard Cats, Common Palm Civets, and Wild Pig) within the plantations, of which Leopard Cats made up 82% of the total number of observations. We found that Leopard Cat habitat use was higher with increased understory vegetation, but that there was no effect of the vegetation treatments on rat abundance or rat damage. There was also a trend for reduced rat abundance with increased Leopard Cat activity. These results show that management practices can significantly affect Leopard Cat habitat use, with potential benefits for pest control. They also highlight the value of large-scale long-term manipulative experiments for developing more sustainable management practices in oil palm.